identificação De Mamiferos Silvestres Do Pantanal Sul- Matogrossense Portadores De Brucella Spp - Eduardo Miguéis Corrêa (2010)
Brucellosis is an anthropozoonosis with worldwide distribution, caused by gram-negative bacteria coccobacilus. The genus Brucella infects different animal species, wild and domestic, as well as humans. This study analyzed blood samples of seven species of wild mammals, collected from properties located in the sub-region Nhecolândia in the Brazilian Pantanal, using the polymerase chain reaction assay. Positive results were obtained for the research of gene virB5 Brucella spp. 7.1% (1 / 14) samples of Thrichomys pachyurus (Sauiá) in 34% (11/32) Nasua nasua (coati), 24% (15/61) of Ozotocerus bezoarticus (pampas deer), 12% (3 / 25) of Cerdocyon thous (cub), 50% (1/2) and 67% (2/3) of Leopardus pardalis(Ocelot). These results indicate that these species can be infected by Brucella species present in animal populations of wetland and the impact of brucellosis in wildlife as the importance of these animals in the brucelose epidemiologic chain needs to be better evaluated.